2017
DOI: 10.1111/anae.14000
|View full text |Cite
|
Sign up to set email alerts
|

Onset of labour epidural analgesia with low‐dose bupivacaine and different doses of fentanyl

Abstract: This study investigated the effects of different doses of epidural fentanyl on the time to onset of epidural analgesia in women in early labour. We hypothesised that onset of epidural labour analgesia (the primary outcome defined as time in minutes from completion of epidural bolus to the first uterine contraction with a numeric pain rating scale [NPRS] score ≤ 3) would be faster with 100 μg of fentanyl epidural bolus compared with 20 μg or 50 μg. Epidural labour analgesia was initiated with 20 μg of fentanyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…Kalra et al 13 found a potency ratio of 1:10 between sufentanil and fentanyl for epidural labor analgesia. Hence, the result of the initiating sufentanil dose in our study and fentanyl 20 μg used by Vedagiri Sai et al 12 may have the same analgesic efficacy with fewer adverse effects. Bernard et al 14 also found that a reduction in sufentanil concentration to 0.156 μg/mL could decrease the pruritus intensity without impeding the quality of labor analgesia, and their recommended sufentanil concentration was close to that of the present study.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Kalra et al 13 found a potency ratio of 1:10 between sufentanil and fentanyl for epidural labor analgesia. Hence, the result of the initiating sufentanil dose in our study and fentanyl 20 μg used by Vedagiri Sai et al 12 may have the same analgesic efficacy with fewer adverse effects. Bernard et al 14 also found that a reduction in sufentanil concentration to 0.156 μg/mL could decrease the pruritus intensity without impeding the quality of labor analgesia, and their recommended sufentanil concentration was close to that of the present study.…”
Section: Discussionsupporting
confidence: 49%
“…This was not the first time that such a small dose of opioids was used for epidural initiation in the early first stage of labor analgesia. Vedagiri Sai et al 12 used a minimal fentanyl dose of 20 μg for epidural initiation with 10 mL of 0.08% bupivacaine in the early first stage, and the median onset time was 18 minutes with a high success rate. Although these investigators found that administration of 50 and 100 μg of fentanyl could reduce the onset time without increase in the adverse effects, fetal bradycardia incidence did increase compared with that of the 20 μg of fentanyl group.…”
Section: Discussionmentioning
confidence: 99%